ANALISIS AUDIT FUNGSI POAC DALAM PENGELOLAAN MANAJEMEN SEKOLAH DASAR DI UPTD SDN 116 ALLU - Ibrahim; Suhardiman Sunusi; Suardi; Idawati (STKIP Subang, 2026)
This study aims to analyze the implementation of the management functions Planning, Organizing, Actuating, and Controlling (POAC) and to evaluate the scope of elementary school management at UPTD SDN 116 Allu, Maros Regency. The research employed a descriptive qualitative approach using audit-based analysis. Data were collected through interviews, questionnaires, observations, and document analysis involving the principal, teachers, and educational staff. The results indicate that the planning and organizing functions have been implemented relatively well through structured school programs and clear division of tasks. However, the actuating and controlling functions still face challenges, particularly in coordination, consistency of program implementation, and systematic follow-up of evaluation results. In terms of management scope, the school has managed curriculum, students, educators and staff, facilities, finance, public relations, and inclusive services adequately, although integration among management functions has not been fully optimized. This study concludes that strengthening data-based planning, improving managerial documentation, and enhancing supervision mechanisms are necessary to support sustainable and effective school governance